Improving the in vitro Degradation, Mechanical and Biological Properties of AZ91-3Ca Mg Alloy via Hydrothermal Calcium Phosphate Coatings - Ali, Asif; Ikram, Fakhera; Iqbal, Farasat; Fatima, Hira; Mehmood, Azra; Kolawole, Maruf Yinka; Chaudhry, Aqif Anwar; Siddiqi, Saadat Anwar; Rehman, Ihtesham Ur (Frontiers in Materials, 2021)
For many years, calcium phosphate coatings to tailor the degradation behavior of magnesium and magnesium-based alloys for orthopaedic applications have received lots of research attention. However, prolong degradation behavior, its effect on biological and mechanical properties as well as osteoblastic response to single-step hydrothermally deposited calcium phosphate coatings remain poorly documented. In this study, Alamar blue assay, cell attachment, live/dead assay, and real-time qRT-PCR was done to study the biological response of the coatings. Furthermore, immersion testing in SBF for 28 days and compression testing of the degraded samples were carried out to examine the degradation behavior and its effect on mechanical properties. The results indicated that coatings have significant influence on both the substrate performance and structural integrity of coated AZ91-3Ca alloy. Immersion test revealed that coating deposited at pH 7, 100℃ (CP7100) improves the hydrogen evolution rate by 65% and the degradation rate by 60%. As the degradation performance of coated samples improves so does the mechanical strength. CP7100 samples successfully retained 90% of its compressive strength after 14 days of immersion while bare AZ91-3Ca alloy lost its mechanical integrity. Furthermore, biological studies show that cells are happily proliferating, differentiating, and adhering to the coating surfaces, which indicates, improved osteointegration and osteogenesis with no sign of alkaline poisoning. RT-PCR results showed that calcium phosphate coatings enhanced the mRNA levels for RUNX2, Col1A, and ALP that may exhibit a speedy bone recovery. Thus, calcium phosphate coatings produced via a single-step hydrothermal method improve the degradation behavior, mechanical integrity and stimulate the differentiation of osteoblast lining. This leads toward faster bone regeneration, which shows a great potential of these coatings to be used on degradable implants as a bioactive protective layer.